MRI T2 signal intensity and tumor response in patients with GH-secreting pituitary macroadenoma: PRIMARYS post hoc analysis. Issue 3 (March 2019) - Bonneville, Fabrice; Rivière, Louis-David; Petersenn, Stephan; Bevan, John S; Houchard, Aude; Sert, Caroline; Caron, Philippe J; ,
Abstract : Objective: Pituitary adenoma MRI T2 signal intensity associates with tumor characteristics including responsiveness to somatostatin analogs (SSAs). These analyses determined whether baseline T2 signal intensity predicts response to primary medical treatment with long-acting SSA. Design: Post hoc analyses of the prospective multicenter, open-label, single-arm PRIMARYS study in which patients with treatment-naïve GH-secreting pituitary macroadenomas received fixed-dose lanreotide autogel (120 mg) every 4 weeks for 48 weeks. Methods: Associations were investigated between adenoma T2-signal hypo/iso/hyperintensity and treatment responses at week 48/last visit: hormonal control (GH ≤2.5 μg/L and IGF-1 normalization); tumor response (tumor volume reduction (TVR) ≥20%); separate GH/IGF-1 control and change from baseline in GH/IGF-1 and tumor volume. Results: Adenomas were hypointense at baseline in 50/85 (59%) patients using visual assessment. Of these, 40% achieved hormonal control and 76% achieved a tumor response. Significant univariate associations arose for hypo- vs isointensity with tumor response and achievement of GH ≤2.5 μg/L, but not IGF-1 normalization or overall hormonal control. In multivariate analysis, tumor response was six times more likely for hypo- vs iso-intense tumors (= 6.15; 95% CI: 1.36–27.88). In univariate change-from-baseline analyses, hypo- vs isointensity was associated with greater TVR and IGF-1 reduction but not change in GH. In multivariate analysis, IGF-1 decreased by an estimated additional 65 μg/L ( P  = 0.0026)) for hypo- vs isointense. Conclusions: Patients with hypointense vs isointense GH-secreting macroadenomas had greater reductions in IGF-1 following primary treatment with lanreotide autogel and were more likely to achieve tumor response. Assessment of T2 signal intensity at baseline may help to predict long-term responses to primary treatment with SSAs.